The Impact of Livestock Cage Condition on Public Health at Livestock Areea in Negarayu Village on Tonjong Region of Brebes Regency. - Zakiyus Sabila, Misna; Kasmini H, Oktia Woro; Indriyanti, Dyah Rini (Public Health Perspective Journal, 2018)
A farm in public area can give bad effect for public health. The appearance of sigh about bad effect of this poultry farming business because it still many breeders disregarding the disposal handling from their business for example feces and food residue causing bad smell and can generate some disease for public. The purpose research to analyze the effect of livestock cage condition to public health at livestock area of Negarayu Village, Tonjong District, Brebes Regency in 2017. This research was quantitative research type. Research design used analytic survey with cross-sectional.The population of 264 families of farmers and a sample of 160 samples obtained by Consecutive Sampling. The instruments used were questionnaires and interviews. analysist using Chi Square test with degree of significance 5% (ÃŽÂ± = 0,05). Result of this research shows there is significant relationship between livestock cage hygiene and Acute Respiratory Infections (p = 0.022), Scabies (p =0.015). There is no significant relationship between livestock cage hygiene with diarrhea (p =0.610). There is significant relationship between livestock cage condition with Acute Respiratory Infections (ARI) (p =0.000), Scabies (p =0.003). There is no significant relationship between livestock cage condition with diarrhea (p =0.966) at livestock area of Negarayu village, Tonjong, Brebes. The conclusion that the community at livestock area of Negarayu village, Tonjong, Brebes more than affected by acute respiratory infection and scabies disease.